1992
DOI: 10.1177/095968369200200208
|View full text |Cite
|
Sign up to set email alerts
|

Global Surface Air Temperature Variations During the Twentieth Century: Part 1, Spatial, Temporal and Seasonal Details

Abstract: This paper is an up-to-date review of instrumentally-recorded, seasonal, surface temperature change across the land and marine regions of the world during the twentieth century. This is the first part of a two part series. The second part will deal with the interpretation of proxy-climate data in terms of large-scale hemispheric or global-scale temperature averages for the Holocene.In Part 1, we review the uncertainties associated with combining land and marine instrumental records to produce regional-average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
1
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 280 publications
(182 citation statements)
references
References 31 publications
8
170
1
2
Order By: Relevance
“…The contour increment for surface temperature (SfcT) is 0.2°C, and regions of insufficient data are not shaded. The combined surface temperature data are those used in the IPCC assessments (also see Jones and Briffa, 1992;Parker et al 1994). When the NAO is high we observe, for example, raised surface temperatures over Eurasia because the warming influence of the ocean is advected more strongly downstream.…”
Section: Precipitation and Stormsmentioning
confidence: 97%
“…The contour increment for surface temperature (SfcT) is 0.2°C, and regions of insufficient data are not shaded. The combined surface temperature data are those used in the IPCC assessments (also see Jones and Briffa, 1992;Parker et al 1994). When the NAO is high we observe, for example, raised surface temperatures over Eurasia because the warming influence of the ocean is advected more strongly downstream.…”
Section: Precipitation and Stormsmentioning
confidence: 97%
“…The evidence of a gradual warming trend in global mean temperature Jones and Briffa 1992;Jones 1994) has also led to a heightened attention to changes in climate variability in recent decades. Climate models indicated that temperature changes are sufficiently large to have corresponding changes in the frequency of extreme events .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the TP has been warming over recent years (Jones and Briffa, 1992;Liu et al, 2000;Guo and Wang, 2011). However, the seasonal and spatial warming trends are different.…”
Section: Discussionmentioning
confidence: 99%